Pengembangan Bahan Ajar Literasi Finansial untuk Siswa Sekolah Dasar - Suprananto Suprananto; Eviana Hikamudin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Financial literacy is one of the competencies needed by elementary school students today, but in reality there are not many financial literacy teaching materials available for elementary schools. The purpose of this study is to develop a game-based learning application that is able to improve the competence of elementary school students in financial literacy. The method used in this study is the instrument analysis method by applying the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results obtained from this study are an android-based application that can improve student competence in financial literacy called Q-VICI Pratama which is suitable for grade IV, V, and VI elementary school students. The implication of the results of this study is the need to collect information from users, students and teachers further as feedback for the evaluation and development of the instrument. In addition, it is necessary to expand financial literacy materials for the next level.